Pengaruh Pendidikan Kesehatan Kontrasepsi Pria terhadap Motivasi Pria PUS menjadi Akseptor KB Vasektomi - Yulia M. Nur; Yade Kurnia Sari; Dewi Harwita (Jurnal Akademika Baiturrahim Jambi, 2023)
Awareness of men becoming KB (Family Planning) acceptors is still low, influenced by the low knowledge of men about family planning and male contraceptive methods, which are still limited, but also influenced by the lack of socialization and promotion of male family planning, the perception that family planning is only for women, the quality of family planning services inadequate, men's lack of access to information about contraception and limited information about the role of men in family planning. The purpose of this study was to determine the effect of health education on male contraception on the motivation of EFA men to become vasectomy family planning acceptors. This research method is a Quasi Experiment One Group Pretest Posttest Design on 35 EFA men (Pupes of Childbearing Age) who are not family planning acceptors. Data was collected by distributing questionnaires to assess men's motivation for EFA. The statistical test used is the Wilcoxon Signed Ranks Test. Samples were taken as many as 35 people. The results of this study indicate that most respondents (54.3%) still have low motivation before being given health education about vasectomy contraception. Most of the respondents (62.9%) already have high motivation after being given health education about vasectomy contraception. Conclusion: there is an effect of health education on the motivation of EFA men to use vasectomy contraception with p value 0.000 <0.05.